2015
DOI: 10.1016/j.jpha.2015.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, characterization and biological studies of phytochemicals from Mammea suriga

Abstract: The present work involves extraction of phytochemicals from the root bark of a well-known Indian traditional medicinal plant, viz. Mammea suriga, with various solvents and evaluation of their in vitro antimicrobial and antioxidant activities using standard methods. The phytochemical analysis indicates the presence of some interesting secondary metabolites like flavonoids, cardiac glycosides, alkaloids, saponins and tannins in the extracts. Also, the solvent extracts displayed promising antimicrobial activity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 29 publications
5
52
0
Order By: Relevance
“…Presence of these functional groups can be attributed to the presence of alkaloids, flavonoids and polyphenol-containing phytochemicals in the leaf extracts of P. juliflora (Kareru et al 2007;Poojary et al 2015). In this study, FT-IR spectral analysis of the root bark extracts of P. juliflora and E. leptostachya showed the presence of phytochemicals carrying a hydrogen bonded -OH functional group.…”
Section: Fourier Transform Infrared Characterisation Of Plant Extractssupporting
confidence: 52%
See 1 more Smart Citation
“…Presence of these functional groups can be attributed to the presence of alkaloids, flavonoids and polyphenol-containing phytochemicals in the leaf extracts of P. juliflora (Kareru et al 2007;Poojary et al 2015). In this study, FT-IR spectral analysis of the root bark extracts of P. juliflora and E. leptostachya showed the presence of phytochemicals carrying a hydrogen bonded -OH functional group.…”
Section: Fourier Transform Infrared Characterisation Of Plant Extractssupporting
confidence: 52%
“…All extracts exhibited the presence of a broad peak for hydrogen bonded -OH stretching in the functional group region. Presence of this functional groups can be attributed to the presence of alkaloids, flavonoids and polyphenols-containing phytochemicals in the root and bark extracts of E. leptostachya (Poojary, Vishnumurthy & Adhikari 2015). http://www.jomped.co.za…”
Section: Fourier Transform Infrared Characterisation Of Plant Extractsmentioning
confidence: 99%
“…Later on, it has also been isolated and studied in different sources like the phylloplane of rice, sugarcane, etc. (Poojary et al, 2015). FT-IR spectra of both the extracts showed peaks at 3392.47 cm -1 and 3425.37 cm -1 which could be due to the OH functional group present in the samples (Tejado et al, 2007).…”
Section: Discussion:-mentioning
confidence: 90%
“…The various functional groups responsible for the biological activities of the crude yeast extracts were recorded (Poojary et al, 2015). KBr pellets of the dried yeast extracts were prepared and the spectra were recorded ranging from 4000-400 cm -1 at a resolution of 2 cm -1 using a FTIR spectrophotometer (NICOLET 6700, USA).…”
Section: Fourier Transform Infrared Radiation (Ftir) Analysis Of Yeasmentioning
confidence: 99%
“…It is already reported that hydroxyl functionality is an integral part of most of the phenolics such as flavonoids and tannins. 38 Moreover, recent studies also show that sev- eral plant products, including polyphenolic substances (e.g., flavonoids and tannins) and various herbal extracts, show antioxidant [39][40][41][42] and antiinflammatory activities. 42 Our results revealed that the extract contains various bioactive functional groups, viz.…”
Section: Resultsmentioning
confidence: 99%